Enhancing nutritional value in fruit crops through biofortification: A comprehensive review - SHARMA, REETIKA; BAKSHI, PARSHANT; KUMAR, RAKESH; SHARMA, ARTI; MAANIK; THAKUR, NIKHIL; KUMAR, VIJAY; GHEWARE, KEDAR MAHADEV (The Indian Journal of Agricultural Sciences, 2023)
Achieving the UN Sustainable Development Goal 2 (UN-SDG2) of eradicating all forms of hunger by 2030 is a formidable yet imperative challenge, given the constrained timeline and the adverse global repercussions of hunger on health and socio-economics. Approximately one-third of the global population suffers from malnutrition or hidden hunger due to micronutrient deficiencies, posing a severe hindrance to economic progress. This has prompted numerous nations to create solutions that could aid in the fight against malnutrition and covert hunger. Food supplementation and dietary diversity are two interventions that are being used. However, the most effective fortification, particularly biofortification, has been predicted to lasting remedy for unmet hunger and malnutrition. To address this issue, the strategy of fruit crop biofortification through gene stacking, employing a judicious blend of traditional breeding and metabolic engineering techniques, holds the potential for significant progress in the next decade. To realize this goal, several specific actions and policy measures are recommended. These measures are vital in our collective pursuit of ending hunger, enhancing global health, and fostering economic development by 2030 as outlined in UN-SDG2. This review article highlights recent research findings and the progress made in expanding biofortification to new countries and environments, thus addressing the global challenge of malnutrition.